Representasi Ideologi Feminisme Dalam Lirik Lagu Taylor Swift pada Album “Folklore’’ - Triani, Andini I Mayang; Febrian, Febrian (Penerbit Goodwood, 2025)
Purpose: This study examines feminist ideologies in the lyrics of Taylor Swift's album, Folklore. Research methodology: Using a qualitative descriptive approach and content analysis, the study analyzes three songs—Mad Woman, The Last Great American Dynasty, and Invisible String. The analysis involved identifying phrases depicting women, categorizing them by feminist type, interpreting their meanings, and drawing conclusions. Results: The results of the analysis show that